“They all have a different vibe”: a rhythmanalysis of climbing mobilities and the Red River Gorge as place - Rickly, J.M. (Sage, 2017)
This paper integrates a mobilities perspective and Lefebvre’s notion of rhythmanalysis as a means interrogate place as an entanglement of mobilities, moorings, and rhythms. By investigating one popular rock climbing destination, this paper demonstrates that mobilities invite encounters with and enactments of place such that travel rhythms, everyday rhythms, and natural rhythms coalesce, interrupt, and even emerge anew. Focusing on lifestyle rock climbers (a particular type of lifestyle mobility dedicated to the pursuit of climbing) and events provides evidence for the ways informational and physical mobilities contribute to and even regiment rock climbing travel rhythms, while the everyday rhythms of place illustrate embodiment as crucial to the enfolding of rhythm and mobilities. Building from Lefebvre’s theory of rhythm and Edensor and Holloway’s (2008) re-articulation of its potential for mobilities studies, this paper emphasizes the ongoing relationality of embodied mobilities and bodily rhythms, seasonal rhythms and informational mobilities, collective mobilities and institutional rhythms.